Stimuli-responsive polymeric micelles for drug delivery and cancer therapy - Zhou Q (Dove Medical Press, 2018)
Qing Zhou,1,* Li Zhang,2,* TieHong Yang,1 Hong Wu1 1Department of Pharmaceutical Analysis, School of Pharmacy, Air Force Military Medical University, Xi’an, People’s Republic of China; 2State Key Laboratory of Military Stomatology, Air Force Military Medical University, Xi’an, People’s Republic of China *These authors contributed equally to this work Abstract: Polymeric micelles (PMs) have been widely investigated as nanocarriers for drug delivery and cancer treatments due to their excellent physicochemical properties, drug loading and release capacities, facile preparation methods, biocompatibility, and tumor targetability. They can be easily engineered with various functional moieties to further improve their performance in terms of bioavailability, circulation time, tumor specificity, and anticancer activity. The stimuli-sensitive PMs capable of responding to various extra- and intracellular biological stimuli (eg, acidic pH, altered redox potential, and upregulated enzyme), as well as external artificial stimuli (eg, magnetic field, light, temperature, and ultrasound), are considered as “smart” nanocarriers for delivery of anticancer drugs and/or imaging agents for various therapeutic and diagnostic applications. In this article, the recent advances in the development of stimuli-responsive PMs for drug delivery, imaging, and cancer therapy are reviewed. The article covers the generalities of stimuli-responsive PMs with a focus on their major delivery strategies and newly emerging technologies/nanomaterials, discusses their drawbacks and limitations, and provides their future perspectives. Keywords: nanomedicine, polymeric micelles, stimuli-responsive, drug delivery, cancer therapy